PRONUNCIATION IN SPEAKING SKILL STUDENTS OF ENGLISH EDUCATION DEPARTMENT LANCANG KUNING UNIVERSITY - Syaifullah Syaifullah (Lectura : Jurnal Pendidikan, 2016)
This research was about students’ pronunciation ability in speaking English atUniversity of Lancang Kuning academic year 2015/2016.Type of the research was crosssectional survey design with the aim as an evaluation program. The number of theparticipant of this research were 36 of third semester of English Education DepartmentFaculty of Education and Teachers Training Lancang Kuning University Pekanbaru whichwere selected by using simple random sampling.Instrument was used in this research wasoral test. In collecting the data, the researcher gave the students test on speakingpronunciation in front of the class. The data gained was analyzed by using descriptivestatistic.The researcher found the students’ pronunciation in speaking were medium ; someconsistent phonemic and foreign stress and intonation patterns but the speaker is intelligible.It was proved by their mean score 1,8. In conclusion to get better pronunciation in speakingskill, the lecturer was suggested to find good strategy in teaching speaking English.